Southeastern Mesoamerica : Indigenous Interaction, Resilience, and Change - Figueroa, Alejandro J.; Johnson, Erlend; Goodwin, Whitney A. (Book collections on Project MUSE., 2020)
"Highlights the diversity and dynamism of Indigenous groups that inhabited and continue to inhabit the borders of Southeastern Mesoamerica, that includes parts of present-day Honduras, Guatemala, and El Salvador. Combining archaeological, ethnohistoric, and historic data to understand the long-term sociopolitical and cultural changes that occurred throughout occupation" --